PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) BERBANTUAN VIDIO ANIMASI TERHADAP PEMAHAMAN KONSEP BELAJAR IPA PESERTA DIDIK DI KElAS IV MI DARUL AKHYAR - Silfia; Ferry Perdiansyah; Mawardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This study uses a quantitative method that is used is the Quasi Experiment method. The population subjects in this study were 57 students of class IV MI Darul Akhyar. By taking a sample of two classes, class IV C 28 students as the control class and class IV D 29 students as the experimental class. Pretest in the control and experimental classes. Hypothesis testing was carried out using the t-test of the separated variance type with a significant level of ∞ = 0.05 for n = 55 in the experimental and control classes. Because the results of data processing are obtained t_(count)=1.02 and t_(table) = 1.67, because t_(count)< t_(table) then H_0 is accepted. Thus at the beginning of learning there is an influence on student learning outcomes between the experimental and control classes. While the hypothesis is carried out using the t test with a significant level of ∞ = 0.05 for n = 55 in the control class and the experimental class. Because the data is normal and homogeneous, dk = n_1 = n_2 – 2. Based on the results of data processing, it is obtained t_(count)=6.39 and t_(table) = 1.67, because t_(count )< t_(table) then H_0 is accepted.